Design and fabrication of escalator model for educational purpose / Ahmad Harith Abdullah - Abdullah, Ahmad Harith (2022)
A lot of people nowadays know about escalators but did not know how escalators work. Most of them do not get a chance to see behind the scenes how escalators are functioning from the inside. By making an escalator model of a reasonable size it will ease people in learning how the machines work. A better understanding of this machine will help to improvise its weakness or even build more advanced machines by using this as a starting platform. The model is user-friendly for students and lecturers or anyone in the educational environment to learn more about the mechanical property of this machine. The main objective is to investigate the crucial key of an escalator, design a model that suits people’s demand and try to build it as close as possible to the expected finished product. Material involved in this project are aluminum, sheet metal, acrylic glass, metal rod, and chain as these materials are easy to find and affordable. Expected fabrication process involved will be gluing, cutting, drilling and sheet metal forming. This model could be beneficial for anyone who is interested to gain an understanding of this machine.